Pendampingan Masyarakat Pada Perencanaan Desain Awal dalam Rangka Peningkatan Fungsi Mushala Miftahul Jannah - Moh Nur Sholeh; Undayani Cita Sari; Shifa Fauziyah (Sekolah Vokasi Universitas Diponegoro, 2021)
Planning of drawings as an initial design stage in a building construction are needed as a work reference for contractors and supervisors as well as a description of the work to be carried out as transparency for the owner. This initial design is between the preliminary study and design calculations stage. By predetermining design drawing, then the calculation of the design which referring to the design drawing can be carried out. This calculation includes the endurance of the structure and its Budget Plan. Currently, there are many necessities of mosque renovation in line with population growth in both urban and rural areas. A prayer room in a village needs renovation because during holidays such as Idhul Fitri, prayer cannot accommodate congregations. Therefore, the renovation can improve the function of the mosque. Initial planning in a construction work is usually in the form of a simple drawing design which includes 2-dimensional and 3-dimensional drawings. This community service activity integrates the knowledge on campus to be applied in society. One of the 3-dimensional design drawing software is using Google SketchUp. The result of this community service activity is a front and side view plan drawing which is used as a reference in calculating the budget plan and project work methods. The community participates by having discussions regarding the Mushala design so that it can match with the requirements of the community and ease of construction later. In addition, this activity can also increase public knowledge about making designs with Google SketchUp.